Activity rating scales in adult muscle disease: How well do they actually measure?. Issue 1 (11th January 2014) - Seedat, Farah; James, Meredith K.; Rose, Michael R.
ABSTRACT Introduction: In an accompanying study we reported on the content of several activity rating scales that have been used for muscle disease. To further aid in achieving consensus we conducted a systematic review to assess the quality of the 19 activity rating scales designed specifically for muscle disease. Methods: We analyzed the measurement properties and the feasibility of the 19 instruments. Several databases were searched for studies relating to the quality of the instruments under review. Two independent reviewers selected studies and assessed instrument quality using pre‐agreed criteria based on published frameworks. Results: We found that none of the 19 instruments have sufficiently comprehensive reporting of measurement or feasibility performance as would be required by regulatory authorities. Conclusions: Further work is required urgently to address these deficiencies of reporting or acquiring additional data. Until then, there will remain a major barrier for translational research to overcome. Muscle Nerve50: 24–33, 2014